Estudo da dinâmica orbital no processo de envelhecimento de NEAs - Guimarães, Millena Castro [UNESP] (Universidade Estadual Paulista (Unesp), 2021)
This work aims to calculate the solar radiation due to an approximation with the Sun and the accumulated radiation on the surface of an asteroid from the moment it becomes a Near-Earth Asteroid (NEA) until the present moment, in order to estimate the fraction of the space weathering. The asteroid chosen was (162173) Ryugu, the target of the Hayabusa2 mission, which has verified that it has traces of space weathering on its surface. In this way, this work seeks to verify Ryugu’s orbital evolution and the possibility that it has undergone close encounters with the Sun, in addition to computing the radiation accumulated on its surface.This issue was approached through numerical integration of the gravitational problem of N-bodies, in which 7.000 clones were selected from the region of the ν6 resonance, verifying which arrived in Ryugu’s current orbit. It was then analyzed the orbital evolution of the clones that succeeded. It was found that some clones arrived at a distance very close to the Sun, receiving a large amount of radiation at once, and such radiation may have modified their surface in a single event. The accumulated radiation over their lifetime was also analyzed

Este trabalho tem como objetivo computar a radiação solar devida a uma aproximação com o Sol e a radiação acumulada na superfície de um asteroide desde o momento em que ele se torna um Near-Earth Asteroid (NEA) até o presente momento, de modo que se possa estimar o seu grau de envelhecimento espacial (space weathering). Nesta pesquisa, o asteroide escolhido foi o (162173) Ryugu, o qual foi alvo da missão Hayabusa2, tendo sido verificado, na ocasião, que ele apresenta um grau de envelhecimento em sua superfície. Desta forma, este trabalho busca verificar a evolução orbital de Ryugu e a possibilidade de ele ter sofrido encontros próximos com o Sol, além de computar a radiação acumulada em sua superfície. Esta questão foi abordado por meio de integrações numéricas do problema gravitacional de N-corpos, em que foram selecionados 7.000 clones partindo da vizinhança da ressonância ν6, verificando-se quais chegaram na órbita atual de Ryugu. Foi então analisada a evolução orbital dos clones que obtiveram êxito. Verificou-se que alguns clones chegaram a uma distância muito perto do Sol, recebendo uma grande quantidade de radiação de uma única vez, podendo tal radiação ter modificado sua superfície em um único evento pontual. Observaram-se também as radiações acumuladas ao longo de sua vida.
Orbital dynamics study in the process of space weathering of NEAs
Keywords: Near-Earth Asteroid; Space Weathering; (162173) Ryugu; Asteroids Orbits; Space Weathering; Asteróides; Órbitas; Radiação solar